MicroRNA (miRNA) PROFILING IN PROSTATE CANCER CARCINOGENESIS: EXPLORATORY RESEARCH: Exploratory Research - Maria Ulfa; Krisna Murti (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Future research will continue to be carried out in terms of looking for molecular markers involved in the early processes of carcinogenesis, metastasis and therapeutic targets in prostate cancer patients. MicroRNAs (miRNAs) are small noncoding RNAs that contribute to prostate cancer progression by controlling genes involved in the androgen receptor (AR) signaling pathway, ectopic expression of proteins involved in the cell cycle and apoptosis, epithelial-mesenchymal transition (EMT) and metastasis of cancer stem cells (CSCs). This study was an exploratory study, the aim was to assess miRNA expression in low histopathological grade prostate cancer compared with high histopathological grade prostate cancer. The novelty of this research is to assess the 25 most increased (up-regulated) and 25 lowest (down-regulated) miRNAs from 800 types of miRNA. Next, we will analyze the mechanisms and confirm the carcinogenesis of prostate cancer. The research results can be used for further research data, especially for targeted therapy in prostate cancer patients.